OP0027 Hand Osteoarthritis (OA) and the Associations to Mortality and Cardiovascular Events - Data from the Framingham Study. (23rd January 2014) - Haugen, I. K.; Ramachandran, V.; Misra, D.; Neogi, T.; Niu, J.; Yang, T.; Zhang, Y.; Felson, D. T.
Abstract : Background: OA may be influenced by a metabolic phenotype, which may increase risk of cardiovascular (CV) disease. Hand OA is especially likely to be related to metabolic as opposed to mechanical causes. Previous studies have suggested conflicting associations between hand OA and mortality and there has been no exploration of hand OA and specific types of CV disease, which may have different etiologies. Objectives: To study whether hand OA is associated with increased mortality and cardiovascular events in a population-based cohort. Methods: We included participants from the Framingham Heart Study, whose CV events and deaths were adjudicated and subtyped by a panel of cardiologists/neurologists. Subjects were 50-75 years, without rheumatoid arthritis and with available information enabling classification of radiographic (≥1 hand joints with Kellgren Lawrence grade (KLG)>2 without pain) and symptomatic hand OA (≥1 hand joints with KLG≥2 and pain in the same joint). Incident CV events (coronary heart disease, congestive heart failure and/or atherothrombotic brain infarction) were defined among subjects that were free of such events at baseline. We examined whether symptomatic and radiographic hand OA were associated with mortality and incident CV events using Cox proportional hazards models adjusting for age, sex, cohort, body mass index, blood glucose, lipid profile, blood pressure, medication use (lipid-lowering, antihypertensive, antidiabetics, NSAIDs and aspirin), smoking and alcohol (for mortality: also previous cardiovascular events and cancer). We also adjusted for the number of joints in the lower limb with pain as a potential marker for OA related physical inactivity. Results: For analyses on mortality, we included 1348 participants (53.8% women) with mean (SD) age of 62.2 (8.2) years at the time of hand OA assessment, of whom 540 (40.1%) and 186 (13.8%) had radiographic and symptomatic hand OA, respectively. Median (interquartile range) time to death or censoring was 191 (172, 203) months. There was no association between hand OA and mortality (table). Although we did not find a significant relation to incident CV events overall, we found a significant association between symptomatic hand OA and coronary heart disease (table). The association remained after additional adjustment for pain in the lower limb (HR 2.00, 95% CI 0.96-4-15). Conclusions: Symptomatic hand OA was associated with an increased risk of coronary heart disease events, which remained after adjusting for metabolic factors at baseline as well as pain in the lower limb. The association was non-significant for radiographic hand OA, suggesting an effect of pain, which may be a possible marker of inflammation. Disclosure of Interest: None Declared